Analisis Value Stream Mapping (VSM) Dalam Upaya Reduksi Waste Di Lini Produksi - Ramadhan Putra Pratama; Aditya Tri Wardana; Ahmad Shobry Dasopang; Abdurroza Hasibuan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study analyzes the implementation of Artificial Intelligence (AI) in smart manufacturing and its impact on the evolving role of Human Resources Development (HRD) in the Industry 4.0 era. Digital transformation has driven companies to integrate AI into various stages of production, including material requirement planning, machine monitoring, quality control, and real-time data analysis. The adoption of AI has been shown to reduce production errors, improve efficiency, and maintain consistent product quality. These technological shifts also directly influence HRD functions. HRD is no longer limited to administrative tasks but is now expected to understand digital tools, enhance employee competencies, and manage workforce planning through data-driven insights. Literature findings indicate that AI supports faster workflows and strengthens strategic decision-making in human resource management. Therefore, this study highlights that AI integration not only enhances productivity on the production line but also pushes HRD to adapt by developing analytical skills and technological awareness. Such adjustments are crucial for addressing the challenges of modern industries that continue to evolve rapidly.